(untitled) (Research, Society and Development, 2022)
The consumption of beef and buffalo meat is present in several places and cultures in the world, mainly because it is an important source of nutrients of high biological value, however it is necessary that this food is safe, without biological, physical or chemical contamination. Thus, the objective of this work is to evaluate the microbiological and physicochemical conditions of bovine and buffalo carcasses from two legalized slaughterhouses in Macapá, Amapá. Altogether 50 samples were collected through swabs and samples of meat parts, together with the inspection of the State Agricultural Defense and Inspection Agency, later forwarded and analyzed in the laboratories of the Food Science and Technology Nucleus of the Scientific and Technological Research Institute. of the State of Amapá (NUCTAL/IEPA) through the methods Adolfo Lutz (2008) AOAC (2006) and MAPA (1999) following the protocols of the referred nucleus that consists of the Normative Instruction N°62, of the Ministry of Agriculture. For the microbiological analysis, the samples presented total percentages of 6% for E. coli and 2% for Samonella spp. However, the greatest contaminations were for Staphylococcus aureus which reached 50% of the total samples. Regarding the proximate composition, despite the fact that both meats have similarities, great variations in the proportion of fat were observed, which may be influenced by their content in essential amino acids and their digestion.